2020
DOI: 10.7759/cureus.10577
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Challenge in the Emergency Department: A Case of Klebsiella Infective Endocarditis Presenting With Splenic Abscess

Abstract: Infective endocarditis (IE) is a serious bacterial infection of the endocardium and/or heart valves that carries considerable morbidity and mortality. Often presenting with very non-specific symptoms, this disease presents many challenges to the emergency medicine practitioner. A 47-year-old male with no pertinent medical history presented to the emergency department complaining of shortness of breath. He stated that his symptoms had been persistent for the last three weeks and were associated with malaise and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…La tumoración esplénica, reportada por TC, fue considerada como última probabilidad diagnóstica, ya que los tumores esplénicos más frecuentes son fundamentalmente a los adultos de 35-45 años y tienen una incidencia en las autopsias del 1.4% 11 . La infiltración secundaria esplénica por enfermedad linfoproliferativa es más común que la forma primaria y puede estar asociada a patologías como SIDA, constituye el 1-2% de todos los linfomas 12,13 , siendo estos los diagnósticos diferenciales. Además, de acuerdo con la bibliografía los abscesos esplénicos pueden presentarse como lesiones solitarias o multiloculares, sin embargo la mayoría de los abscesos relacionados con endocarditis infecciosa son únicos y corresponden al 5% del total de los abscesos esplénicos reportados (Tabla 1) 5,7 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La tumoración esplénica, reportada por TC, fue considerada como última probabilidad diagnóstica, ya que los tumores esplénicos más frecuentes son fundamentalmente a los adultos de 35-45 años y tienen una incidencia en las autopsias del 1.4% 11 . La infiltración secundaria esplénica por enfermedad linfoproliferativa es más común que la forma primaria y puede estar asociada a patologías como SIDA, constituye el 1-2% de todos los linfomas 12,13 , siendo estos los diagnósticos diferenciales. Además, de acuerdo con la bibliografía los abscesos esplénicos pueden presentarse como lesiones solitarias o multiloculares, sin embargo la mayoría de los abscesos relacionados con endocarditis infecciosa son únicos y corresponden al 5% del total de los abscesos esplénicos reportados (Tabla 1) 5,7 .…”
Section: Discussionunclassified
“…Con base en factores de riesgo, principalmente hemodiálisis, el patrón radiográfico pulmonar asociado a embolia séptica pulmonar por las típicas lesiones en bala de cañón, al igual que la presentación clínica rápidamente progresiva, con evolución a falla orgánica, consideramos altamente probable endocarditis y probable embolia séptica a bazo 13 . Por ello se inició manejo antibiótico enfocado a endocarditis, manejo propio del choque séptico.…”
Section: Discussionunclassified
“…This case is unusual in that to the authors' knowledge, there have been no cases described in the literature of a splenic abscess caused by Clostridium perfringens in which the patient's underlying comorbidities made immediate surgical intervention not possible. Although there is ample data demonstrating success of percutaneous drainage of splenic abscesses and even some reports of using medical therapy alone, none of these cases involve Clostridium perfringens [ 10 , 15 , 16 ]. In our case, percutaneous drainage plus antimicrobial therapy was insufficient in obtaining source control.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Patients often do not demonstrate risk factors or specific symptoms, which makes the diagnosis difficult, especially during current COVID-19 pandemic. [4,5] Until now, reports on COVID-19 patients with IE are limited. Here, this study reported the first confirmed case of COVID-19 with IE presenting MRSA bacteremia and multiple organ embolism, ultimately achieved remission.…”
Section: Introductionmentioning
confidence: 99%